Potential biomarkers of miRNA in non-functional pituitary adenomas - Zhang, Qizhi; Wang, Ying; Zhou, Yinting; Zhang, Qiujuan; Xu, Chuan (World journal of surgical oncology, 2021)
Background The abnormal expression of microRNA (miRNA) has been proved to be closely related to the occurrence and progression of tumors. A unique expression of multiple miRNAs has been found in different types of tumors. However, the correlation between miRNA and non-functional pituitary adenoma (NFPA) is not clear. In this study, miRNAs (miRNA-26b, miRNA-138, miRNA-206, and miRNA-let-7e) have been used as detection genes to compare the miRNA expression levels of NFPA subjects and healthy controls and to explore the expression of four different miRNAs in NFPA. Methods Ten untreated NFPA volunteers were served as subjects, and 10 normal subjects were selected as controls. Peripheral blood samples were collected, and four differentiated expressed miRNAs (miRNA-26b, miRNA-138, miRNA-206, and miRNA-let-7e) obtained in the early stage of the test group were detected, recorded, and archived by quantitative real-time PCR (qPCR). The difference and significance of endogenous miRNA expressions were explored through statistical analysis, hoping to find biomarkers for clinical treatment. Results The levels of miRNA-26b, miRNA-138, miRNA-206, and miRNA-let-7e in the peripheral serum of patients with NFPA were significantly lower than those in normal subjects (P < 0.05). Conclusion miRNA-26b, miRNA-138, miRNA-206, and miRNA-let-7e may be involved in the occurrence and progress of NFPAs. This study aims to study the biological targets of NFPA. It starts from the study of whether miRNA, miRNA-26b, miRNA-138, miRNA-206, and miRNA-let-7e may be tumor suppressor genes in NFPA, which provides a basis for further exploration of tumor markers of pituitary adenoma. Keywords: miRNA, Non-functional, Pituitary adenomas, Biomarkers